Post-temporary ligation intra-operative mesenteric portovenography: comparison with computed tomographic angiography for investigation of portosystemic shunts - Parry, Andrew; White, Robert N. (Wiley, 2018)
Objectives: Comparison of pre-operative computed tomographic angiography and post-temporary full ligation intraoperative mesenteric portovenography for the documentation of the intrahepatic portal vasculature in patients with single extrahepatic portosystemic shunts. Methods: Retrospective study of patients with extrahepatic portosystemic shunts that underwent preoperative computed tomographic angiography and intra-operative mesenteric portovenography after temporary full ligation of an identified shunt vessel. Studies were compared for appearance of the intrahepatic portal vasculature. Results: Fourteen dogs and five cats were included in the study with various single congenital extrahepatic portosystemic shunts variations. With the exception of those shunts involving the right gastric vein, the identification of the intrahepatic arborisation was similar on both modalities. Subjectively, however, there was improved contrast enhancement, as well as slight enlargement of the intrahepatic portal vasculature, on portovenography compared to computed tomographic angiography. Clinical significance: This paper shows that computed tomographic angiography cannot replace intraoperative mesenteric portovenography after temporary full ligation, which provides information regarding the development of intrahepatic portal vascularity. It is a practical and dynamic procedure providing results which are instantaneously available at the time of surgery. In addition, TFL-IOMP confirmed both that the shunting vessel had been recognised and only one vessel was present.